The impact of a bariatric rehabilitation service on weight loss and psychological adjustment - study protocol - Hollywood Amelia; Ogden Jane; Pring Christopher (BMC, 2012)
Abstract Background Bariatric surgery is currently the most effective form of obesity management for those whose BMI is greater than 40 (or 35 with co morbidities). A minority of patients, however, either do not show the desired loss of excess weight or show weight regain by follow up. Research highlights some of the reasons for this variability, most of which centres on the absence of any psychological support with patients describing how although surgery fixes their body, psychological issues relating to dietary control, self esteem, coping and emotional eating remain neglected. The present study aims to evaluate the impact of a health psychology led bariatric rehabilitation service (BRS) on patient health outcomes. The bariatric rehabilitation service will provide information, support and mentoring pre and post surgery and will address psychological issues such as dietary control, self esteem, coping and emotional eating. The package reflects the rehabilitation services now common place for patients post heart attack and stroke which have been shown to improve patient health outcomes. Methods/Design The study is a randomised control trial and patients will be allocated to receive either usual care or the bariatric rehabilitation service pre and post bariatric surgery. Follow up measures of weight loss and psychological issues will be taken at baseline (2 weeks preoperatively), 3, 6 and 12 months postoperatively. The contents of the bariatric service and the follow up measures are based on previous pilot work and have been developed further by the research team working closely with two patient support groups (BOSPA & WLSinfo). This study will take place in St Richard's Hospital in Chichester in the UK. Discussion It is predicted that a bariatric rehabilitation service will improve weight loss following surgery and will also facilitate changes in other psychological variables such as quality of life, dietary control, self esteem, coping and emotional eating. This also has cost implications for the NHS and other healthcare providers as improved effectiveness of bariatric surgery reduces the health costs of obese patients in the longer term. Trial registration ClinicalTrials.gov NCT01264120.